1987
DOI: 10.1080/00039896.1987.9935789
|View full text |Cite
|
Sign up to set email alerts
|

Carcinogenicity of Extract of Airborne Particles Using Newborn Mice and Comparative Study of Carcinogenic and Mutagenic Effect of the Extract

Abstract: An organic extract of airborne particles collected in Tokyo and its fractions (neutral, acidic, and basic) were investigated in Ames Salmonella assays for mutagenicity and in newborn mice for carcinogenicity. Mutagenicity to TA100 and TA98 strains was detected in the whole extract, the neutral, the acidic and the basic fractions with and without metabolic activation. In the carcinogenicity test, the incidence of lung tumor was as follows: whole extract, 4/25; neutral fraction, 7/25; acidic fraction, 0/20; basi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1988
1988
2006
2006

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Sulphur content in feedstock is low (<1%); in addition the high content of calcium oxides in the mineral matter of the raw lignite contributes to negligible releases of sulphur oxides in the flue gases. Thus, dust emissions seem to be the most significant air pollution problem in the area; the measured ambient concentrations of suspended particles are often at high levels exceeding local and international standards [4,5]. The high particulate concentration in this area has been attributed to two parameters: (a) particulates released in the flue gases of the thermal power stations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sulphur content in feedstock is low (<1%); in addition the high content of calcium oxides in the mineral matter of the raw lignite contributes to negligible releases of sulphur oxides in the flue gases. Thus, dust emissions seem to be the most significant air pollution problem in the area; the measured ambient concentrations of suspended particles are often at high levels exceeding local and international standards [4,5]. The high particulate concentration in this area has been attributed to two parameters: (a) particulates released in the flue gases of the thermal power stations.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown correlation between respiratory symptoms and heart diseases with the inhalable particles [2,3]. Particles with a size less than 10 mm (PM10) have long been implicated in causing adverse health effects and increased mortality [4] whereas fine (PM2.5) and ultrafine particles impose even higher risk [5][6][7]. Thus, it is of paramount importance the ability to correlate the sources and chemical composition of aerosols with their biological impact.…”
Section: Introductionmentioning
confidence: 99%
“…A paper by Sasaki et al 2 in 1987 from Japan describing the carcinogenicity of extracts of airborne particles in Tokyo.…”
mentioning
confidence: 99%